Belajar Matematika Sambil Bermain Bersama Siswa Sekolah Dasar dan Sekolah Menengah - Lakapu, Meryani; Dosinaeng, Wilfridus Beda Nuba; Uskono, Irmina Veronika; Jagom, Yohanes Ovaritus; Leton, Samuel Igo; Djong, Kristoforus Djawa (LOSARI DIGITAL, 2023)
The purpose of this activity is to improve students' numeracy skills by using fun methods. This activity starts from situation analysis, activity design, socialization, implementation, and evaluation of activities. The result of this activity is that it can improve students' numeracy skills. Students are faster in solving the problems given. The team hopes that tutoring activities like this can be carried out sustainably in the future. Students gave a positive impression and requested that this teaching and learning activity be sustainable because it really helped them in understanding basic concepts